If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x-3)=2(x-1)+5
We move all terms to the left:
5(x-3)-(2(x-1)+5)=0
We multiply parentheses
5x-(2(x-1)+5)-15=0
We calculate terms in parentheses: -(2(x-1)+5), so:We get rid of parentheses
2(x-1)+5
We multiply parentheses
2x-2+5
We add all the numbers together, and all the variables
2x+3
Back to the equation:
-(2x+3)
5x-2x-3-15=0
We add all the numbers together, and all the variables
3x-18=0
We move all terms containing x to the left, all other terms to the right
3x=18
x=18/3
x=6
| 4m-8=0 | | 71x=192 | | 18y=24y2 | | 3(2x+5)-(x+3)=2 | | 3(2x+3)-7(x-4)=15x-11 | | 48x+4)=176 | | 4(8x+4=176 | | 60/1.4=x | | 60/1.2=x | | 60/1.8=x | | 3x-2(5-x)=30 | | 0.2*60=x | | 0.8*60=x | | 1.2x*60=x | | 1.2x-60=x | | 1.8/x=60 | | 8(4-y)=6(3-y) | | 60*1.8=x | | 60-1.2x=x | | 60*1.2x=x | | a-12=43 | | 60-x=1.2x | | x^2-0.7*x^2=80 | | 60-x=1.4x | | 60-x=1.4 | | 60-x=1.8x | | 1+4x=16-x | | W^2+5w-200=0 | | 3x+4=2(7-2x) | | X^2+40x-319=0 | | 2^x/3=256 | | 7x-65=5 |